Cannibalism in Naticidae from the La Meseta Formation (Eocene, Antarctica). Issue 3 (4th February 2016) - Brezina, S.S.; Cech, N.; Martín Serralta, D.; Casadío, S.
Abstract: Polinices marambioensis is a naticid gastropod which is the most common constituent in fossil accumulations in the upper section of the Cucullaea I Allomember (Middle Eocene) of the La Meseta Formation in James Ross Basin, Antarctic Peninsula. This species was an important predator of infaunal bivalves and gastropods, including other naticids. The aim of this work was to assess the pattern of predation and cannibalistic behaviour of P. marambioensis . A total of 2648 specimens of P. marambioensis were examined for drill holes, which were assigned to Oichnus paraboloides . Drilling frequency data were measured as a proxy for predation intensity and statistical analyses were performed. Further, the site of each drill hole was established according to the morphological features of the shell on each specimen to assess possible preference of predators for the site of perforation. Results suggest that P. marambioensis is an efficient cannibalistic predator for a specific size range of prey (8–22 mm), and drill holes are distributed preferentially in two specific sectors of their shells. This selective cannibalistic prey behaviour in P. marambioensis affected not only the dynamics of their populations but the ecological structure of the community in which they lived.